PENGIKISAN BAHASA DALAM MASYARAKAT JAWA Catatan tentang Proses Kepunahan Bahasa Jawa - Suparta, Hendarto (Fakultas Ilmu Budaya Universitas Diponegoro, 2015)
Will Javanese language die in ten to fifteen years to go? The answer tends to be â€œnoâ€. How about in coming two or three generations? The answer will be â€œpossibly yesâ€. The fact, since the day of the independence declaration of the Republik of Indonesia, Javanese language has been undergoing a process what may be called language obsolescent or language replacement, or language demise or language death, in a certain degree. There are at least two reasons to support the prediction on that undesired destiny of the Javanese language in next generation periods. First, in this global era caused by the speed development of science and technology especially in transportation and communication, half of the total languages in the world, around 6000 languages, were dead in the past three centuries and ten languages will die every year. Some local languages have been replaced by, not many but powerful and dominant international languages, like English, and by national language like Indonesian in Indonesia. In Semarang and possibly other cities in Java not including Surakarta and Yogyakarta, Javanese people rarely speak krama, in a situation where it should be, while at least in rural area where ngoko was used, now in certain domains are replaced by Indonesian language significantly, where the speakers are young generation. Javanese language, said many people, has been a foreign language taught in elementary school to senior high school. Today, however, in informal situation among those who are familiar one with another, especially between people from lower status, lower Javanese or ngoko is still used in many places, and full Javanese (ngoko and krama) is still used in areas such as Demak, Purwodadi, Salatiga, and Pekalongan. This phenomena will unlikely change in 5 to 10 years to go. But no one, I think, will dare to guarantee if people use one to two generations as criterion. Now people with different backgrounds have been without hesitant to choose Indonesian as their childrenâ€™s mother tongue since 30 to 35 years ago, with many different reasons. Two among other reasons are, first, for their childrenâ€™s success in school, and second, parents donâ€™t want their children speak with them using ngoko, so it seems no choice but Indonesian. How about with krama? It is not a secret any more that some parents in Semarang city tend not having communicative competence to speak krama. Entering global era in this reformation period, English language has been used everywhere in this country although actually people still use Indonesian, so what I mean is that that is a case of code-mixing. What is important to note here is that peopleâ€™s attitude toward that foreign language can be considered to endanger the status of Indonesian because of the high status of that foreign language in the situation only few people speak standard Indonesian, an Indonesian prestigious variety. It is clear without saying with the fate of Javanese language if no people are aware with the situation. This article proposes some suggestions to anticipate the situation described above beside the fact that Javanese people are still proud with their culture.